Seed Yield Variation of Rapeseed (Brassica campestris) by Integrated Nutrient Management Practices under Rain-fed Condition of Terai Region in West Bengal, India - De, Biman; Sinha, Biswapati; Ghosh, Mayukh; Sinha, A. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during the winter seasons of 2007-08 and 2008- 09 to study the physiological analysis of seed yield variation of rapeseed (Brassica campestris) as influenced by integrated nutrient management practices. Amongst the different sources of organics (FYM @ 10 t ha-1 and vermicompost, neem cake and poultry manure each @ 5.0 t ha-1), vermicompost @ 5.0 t ha-1 significantly influenced the leaf area index (LAI), dry matter accumulation (DMA), crop growth rate (CGR), net assimilation rate (NAR), yield attributes and yield over other organics. The combined application of organics (FYM @ 2.5 t ha-1, vermicompost, neem cake and poultry manure each @ 1.25 t ha-1) along with 50% recommended dose of fertilizer (60:30:30 kg ha-1 of N:P2O5:K2O, respectively) significantly influenced the LAI, DMA, CGR, NAR, yield attributes and yield.